Transformasi Literasi Siswa dan Profesionalisme Guru Melalui Pengembangan Pembelajaran Teks Deskripsi Berbasis Kearifan Lokal - Ramli, Ratu Bulkis; Ismail, Ismail; Damayanti, Damayanti; Mudatsir, Mudatsir; Hanipah, Sri; Oktariani, Mutiyah; Parman, Parman; Asrudi, Asrudi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The low level of student literacy in understanding descriptive texts and the need to strengthen teacher professionalism constitute the primary foundation of this community engagement program. Instruction on descriptive texts in junior high school of Al Ma’arif NU Merauke has not fully utilized the potential of local wisdom, resulting in students’ limited ability to observe objects in depth and express their observations in coherent descriptive form. At the same time, teachers require systematic collaborative support to enhance their pedagogical competence and to design contextual and meaningful learning experiences. This program employed a two-cycle lesson study model, comprising stages of planning, classroom implementation, observation, and reflection to ensure continuous improvement of instructional practices. Each cycle emphasized the development of teaching materials grounded in local wisdom, the enhancement of classroom interaction quality, and the monitoring of students’ progress in comprehending and producing descriptive texts. The results indicate substantial improvement in students’ ability to generate more detailed, logical, and culturally relevant descriptions. Teachers also demonstrated increased professionalism through collaborative practice, improved reflective capacity, and refined instructional strategies across cycles. These findings underscore that integrating local wisdom through collaborative learning processes is effective in strengthening student literacy and enhancing teacher competence, and holds potential as a sustainable model for instructional development in elementary education.